Pengaruh Zakat sebagai penguran penghasilan kena pajak terhadap tingkat kesadaran masyarakat dalam memenuhi kewajiban zakat (Studi kasus pada Rumah Zakat Daerah Istimewa Yogyakarta). - Fitria Rahmah (EPI 13 UMY 146, 2013)
This research aims to determine the effect of policy implementation of Zakat as a deduction taxable income toward public awareness in DIY to perform Zakat. This research is field research (field research ) with DIY community that include mandatory taxes and obligatory Zakat at Rumah Zakat as a research subjects, while the object of this research is the effect of Zakat as a reduction of taxable income. This research instrument using observation and interviews, and using the form of interviews and direct data that obtained from Rumah Zakat as primary data, and secondary data obtained from the Rumah Zakat's official website , and a thud literature , articles and previous research . The results of this research is , government policies related to income tax deduction as a charity does not affect the DIY community awareness in performing Zakat , this is caused by Zakat function as a deduction only reduces the small amount of tax to be paid , the lack of public confidence in the tax management institutions , some people who work in private institutions or in state/local enterprises which implement Law No. 36 of 2008 Section 21 (where the employee income tax withheld by the institution where they work) income/salary they received was deducted directly by the relevant institution , so it will be complex when the taxpayer must take care of attaching proof of payment of Zakat , some people with hectic work hours does not want to concern in the process of taking, calculating and attaching proof of payment of Zakat, and prefer to pay them full . Keyword : Zakat, tax , Awareness